DISCRIMINATION, EMOTION, AND HEALTH INEQUITIES - Fourie, Carina (Les ateliers de l'éthique / The Ethics Forum, 2018)
In this paper I argue that certain ways in which the relationship among discrimination, emotions and health is presented can undermine equity. I identify a model of this relationship the discrimination-emotion-health model - and claim that while the model is important for understanding the detrimental impact that discrimination and oppression can have on emotions and health, certain implications of the model are troubling. I identify six critiques of the model, and show that equity could be undermined, for example, when stereotypes of the oppressed are reinforced and the experiences of the privileged are normalized. I then assess the implications of my analysis of the model and its critique for a framework of health equity, demonstrating what such a framework would need to look like in order for it to best represent discrimination as a psychosocial determinant of health.